A Decentralized Higher Order Sliding Mode Control for Islanded Photovoltaic-Storage Systems. (15th September 2022) - Rosini, A.; Procopio, R.; Bonfiglio, A.; Incremona, G.P.; Ferrara, A.
Abstract: Sustainable energy transition, air pollution reduction and climate change mitigation are the most challenging themes in nowadays energy sector. Microgrids (MGs) are one of the most effective ways to integrate Renewable Energy Sources (RES), and among them PhotoVoltaic (PV)-Storage (ST) configuration is relevantly promising. Focusing the attention on the PV and ST converters primary control, the main needs are to properly regulate voltage and frequency and optimally exploit the energy coming from the sun and manage the ST operation without any communication among the converter controllers. The conventional converter control approach presents several drawbacks and thus a strategy based on Higher Order Sliding Mode (HOSM) is presented in this work. The HOSM converter control strategy is fully analysed defining its control laws and the control schemes. A comparison between the HOSM and conventional control is performed with dedicated simulations on a common benchmark MG in order to highlight the advantages of the proposed strategy. Highlights: Decentralized control of islanded photovoltaic-storage microgrids. Higher-Order sliding model application to microgrids. Robust control approach for islanded power systems. Combined results of primary and secondary frequency regulation without communication.